2018
DOI: 10.1016/j.polymdegradstab.2018.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Flame retardancy effect of combined ammonium polyphosphate and aluminium diethyl phosphinate in acrylonitrile-butadiene-styrene

Abstract: Portal del coneixement obert de la UPC http://upcommons.upc.edu/e-prints Aquesta és una còpia de la versió author's final draft d'un article publicat a la revista Polymer Degradation and Stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 38 publications
8
31
0
Order By: Relevance
“…Guo et al [32] studied the influence of modified ammonium polyphosphate (APP) on the flame retardancy of wood floor composite by cone calorimetry and noticed a synergetic effect between APP and the composite followed by a good improvement on the overall flame retardancy of the multicomponent material. Similar results were outlined also by other research groups (please see for example Realinho et al [1], Xia et al [26], Lu et al [27], Despinasse and Schartel [28], Ma et al [33]).…”
Section: Introductionsupporting
confidence: 88%
See 3 more Smart Citations
“…Guo et al [32] studied the influence of modified ammonium polyphosphate (APP) on the flame retardancy of wood floor composite by cone calorimetry and noticed a synergetic effect between APP and the composite followed by a good improvement on the overall flame retardancy of the multicomponent material. Similar results were outlined also by other research groups (please see for example Realinho et al [1], Xia et al [26], Lu et al [27], Despinasse and Schartel [28], Ma et al [33]).…”
Section: Introductionsupporting
confidence: 88%
“…Several formulations were prepared (see Table 2) and all the materials were first dried at 100 C for 24 h than were mixed at a blending temperature of 205 • C in a Brabender mixing chamber (Brabender, Germany), with a rotating rate of 60 rpm applied for 10 min. The materials final composition was chosen according to the open literature [1][2][3][4][5] and with the scope to determine the most favorable minimum addition of OMT and fire retardants in order to get the best fire properties. The specific specimens used for further tests were obtained at 205 • C in a Carver press over three minutes at a pressure of 50 atm and two minutes at 150 atm.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that nanocomposites with 30 phr APP achieved the flammability rating of V‐1 and limiting oxygen index (LOI) of 29.2% and also had the highest thermal stability. Realinho and fellows reported that condensed‐phase activity via charring and residue formation in acrylonitrile‐butadiene‐styrene copolymer containing APP was observed. Rajaei investigated the combined effects of APP and talc on the fire and mechanical properties of epoxy/glass fabric composites.…”
Section: Introductionmentioning
confidence: 98%